Comparative Evaluation of Pitavastatin and Lovastatin on the Incidence and Progression of Rheumatoid Arthritis in Type II Collagen-induced Rat Model - Jithin Mathew (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder marked by persistent joint inflammation, cartilage degradation and disability. Statins commonly prescribed for hyperlipidemia have demonstrated potential immunomodulatory activity; however, their role in RA pathogenesis remains uncertain. Objective: The present study examined the impact of pitavastatin and lovastatin on RA onset and progression using type II collageninduced arthritis (CIA) experimental model. Methods: CIA was induced in rats, which then received pitavastatin or lovastatin for a period of 42 days. Clinical evaluation included measurement of paw volume, monitoring of body weight and calculation of the arthritic index at regular intervals. On day 42, retro orbital blood samples were collected to determine rheumatoid factor (RF), white blood cell (WBC) count, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and red blood cell (RBC) count. Results: Significant decline in body weight was observed in lovastatin-treated animals from day 35 post-immunization compared with other groups. Both statin-treated groups demonstrated increased paw swelling and higher arthritic index values relative to controls. Hematological findings indicated elevated RF, WBC count, ESR and CRP levels, accompanied by a reduction in RBC count in all statin treated animals. These changes were more marked with lovastatin, which appeared to accelerate arthritis progression and symptom manifestation compared with pitavastatin. Conclusion: Statin administration, particularly with lovastatin, may predispose to RA development and intensify disease severity. These results underscore the importance of cautious statin use in individuals at risk of autoimmune joint disorders.